Smart grids and internet of things : an energy perspective - Sanjeevikumar, Padmanaban, 1978-; Dhanaraj, Rajesh Kumar; Sathyamoorthy, Malathy; Holm-Nielsen, Jens Bo; Balusamy, Balamurugan (John Wiley & Sons, Inc., 2023)
SMART GRIDS AND INTERNET OF THINGS Smart grids and the Internet of Things (IoT) are rapidly changing and complicated subjects that are constantly changing and developing. This new volume addresses the current state-of-the-art concepts and technologies associated with the technologies and covers new ideas and emerging novel technologies and processes. Internet of Things (IoT) is a self-organized network that consists of sensors, software, and devices. The data is exchanged among them with the help of the internet. Smart Grids (SG) is a collection of devices deployed in larger areas to perform continuous monitoring and analysis in that region. It is responsible for balancing the flow of energy between the servers and consumers. SG also takes care of the transmission and distribution power to the components involved. The tracking of the devices present in SG is achieved by the IoT framework. Thus, assimilating IoT and SG will lead to developing solutions for many real-time problems. This exciting new volume covers all of these technologies, including the basic concepts and the problems and solutions involved with the practical applications in the real world. Whether for the veteran engineer or scientist, the student, or a manager or other technician working in the field, this volume is a must-have for any library. Smart Grids and Internet of Things: Presents Internet of Things (IoT) and smart grid (SG)-integrated frameworks along with their components and technologies Covers the challenges in energy harvesting and sustainable solutions for IoTSGs and their solutions for practical applications Describes and demystifies the privacy and security issues while processing data in IoTSG Includes case studies relating to IoTSG with cloud and fog computing machine learning and blockchain.